2022
DOI: 10.1037/dev0001344
|View full text |Cite
|
Sign up to set email alerts
|

The codevelopment of reading and attention from middle childhood to early adolescence: A multivariate latent growth curve study.

Abstract: Attention skills are strong cross-sectional predictors of reading comprehension from childhood through to adolescence. However, less is known about the developmental relations between these two domains across this period. This study examined the codevelopment of reading and attention in a community sample of 614 Australian school students (50% female). Reading and attention were assessed at ages 8, 10, 12, and 14. Results of univariate latent growth models demonstrated, on average, curvilinear trajectories for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 67 publications
3
13
2
Order By: Relevance
“…While these results run counter to public narratives of educational decline (e.g. Kelly, 2021) they do align with prior empirical research which has found compensatory growth in reading (Larsen et al, 2022;Ricketts et al, 2020;Shin et al, 2013;Wang et al, 2017) and math (Larsen et al, 2022;Neuendorf et al, 2020;Shanley, 2016;Wang et al, 2017) across similar age spans to that examined by this study. Nonetheless, our finding of compensatory growth in NAPLAN assessments does not necessarily indicate that Matthew effects will never arise in the academic domains, and over the age span investigated by this study.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…While these results run counter to public narratives of educational decline (e.g. Kelly, 2021) they do align with prior empirical research which has found compensatory growth in reading (Larsen et al, 2022;Ricketts et al, 2020;Shin et al, 2013;Wang et al, 2017) and math (Larsen et al, 2022;Neuendorf et al, 2020;Shanley, 2016;Wang et al, 2017) across similar age spans to that examined by this study. Nonetheless, our finding of compensatory growth in NAPLAN assessments does not necessarily indicate that Matthew effects will never arise in the academic domains, and over the age span investigated by this study.…”
Section: Discussioncontrasting
confidence: 63%
“…Compared with studies examining primary school grades, fewer studies have examined reading development from middle childhood through to adolescence. Across these later age spans compensatory growth patterns are more commonly identified (Larsen et al, 2022;Ricketts et al, 2020;Shin et al, 2013;Wang et al, 2017). These inconsistent results may be partly attributed to the variety of measures used to capture "reading" and the different age ranges of samples under investigation (Parrila et al, 2005): it is possible that different subcomponents of reading follow different developmental patterns and these may be obscured if assessments of several skills are aggregated, particularly in the early school grades (Paris, 2006).…”
Section: Mathematics Development Similar To Research On Reading Compr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses covaried for sex (males = 0 and females = 1) and socioeconomic status (SES). SES was represented by a single factor score, as detailed in [22]. Among the five items included on the factor were the highest level of education and occupation reported by both parents and the family home's neighbourhood SES.…”
Section: Methodsmentioning
confidence: 99%
“…It is the cycle from poor skills to limited enjoyment that manifests into the Matthew Effect, wherein the weaker students fall further behind over time on account of less leisure reading, while the stronger performing students have their skills subsequently reinforced by more leisure reading, which escalates into increasingly stronger achievement over time. There are claims that the Matthew Effect perpetuates throughout schooling, but the effects are arguably short lived, as is evidenced in the literature [22] and detailed below.…”
Section: Plos Onementioning
confidence: 99%